Formation of compensation policy in modern conditions of national economy development (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The development of the national economy requires modern enterprises to build and implement a new compensation policy through innovative approaches to the formation of wages and incentive mechanism.The purpose of the article is the theoretical substantiation of the essence of compensation policy and the development of directions of its formation on the basis of the organization of wages and motivational mechanism, regulation at the state and contractual levels, the level of the enterprise.Methods. The article uses a monographic method, analysis, method of generalization of scientific approaches.Results. The article provides a theoretical analysis of scientific thought on the interpretation of the concepts of "compensation" and "compensation policy". The author's approach to the definition of "compensation policy" is formed. The study of the essence of compensation policy allows to interpret it as an activity at different levels of government (state, industry, regional, enterprise and organization, interpersonal) to form the conditions of remuneration and motivational mechanism to achieve strategic goals of social and labor relations.The foreign experience of the organization of the compensation system is considered. The influence of compensation policy on the competitiveness of personnel and the enterprise as a whole is determined. The directions of wage formation at the state and contractual levels as an important component of compensation policy in modern conditions of national economy development are developed.Conclusions. The study allows to generalize scientific approaches to the concept of "compensation policy" and suggest directions for its development, which will help ensure the competitiveness of staff, enterprises, the region, the national economy as a whole.